103 - SOCIOECONOMICS CHARACTERISTICS AND USE OF NUTRICIONAL ERGOGENICS AIDS FOR PRACTICING ADOLESCENTS OF STRENGTH TRAINING, PETRÓPOLIS (Fiep Bulletin - online, 2011)
The recovery of the body in contemporary society has mobilized many people engaged in physical activity. With a view to obtaining a perfect body, many people physically active use nutritional ergogenics aids to increase muscle mass and improving the aesthetics, especially the male population. The aim of this study was to know about their socioeconomics characteristics and use of nutritional ergogenics aids for practicing adolescents of strength training who attend four gyms, Petrópolis. This study is a cross-sectional descriptive study with adolescents enrolled in four gyms located in the city of Petrópolis, between 13 and 19 years, who agreed to participate in this research during May 2009. Of the 50 adolescents registered, it was discovered that all are students, male, average age (±SD) of 16.74±1.49 years. About use of nutritional ergogenics aids, we found that 28% of adolescent reported to use and 72% did not report. It was found that 33.3% were using Whey Protein®, Creatine 22.2%, 11.1% Albumin, 27.8% other ergogenics aids proteins and 5.6% of Maltodextrin. We concluded that about 30% of adolescents reported to consume nutritional ergogenics aids.
Keywords: Ergogenic Aid; Strength Training; Adolescent